Faktor-Faktor yang Mendorong Kejadian Rabies pada Anjing di Desa-Desa di Bali (FACTORS ENCOURAGING THE INCIDENCE OF RABIES IN DOGS IN VILLAGES IN BALI) - Batan, I Wayan; Suatha, I Ketut (Jurnal Veteriner; Vol 17 No 2 (2016), 2016)
Rabies has been spread to all over part of Bali, caused 160 people and thousands of dogs’ death. Theeffort for preventing rabies have been done, many villages after six months of eradicating rabies programmedhave been free, but a few villages still infected with the rabies. The aim of the study was to find the factorsthat make a number of villages are still infected with rabies. The study was conducted by doing a fieldsurvey to the nine districts of Bali. The survey was aimed at villages that remain infected despite effortsto control rabies has been done in the village. The device of survey is equipped with open ended and closedended questionnaire to be asked to the respondents. Characteristic villages infected with rabies will befigured out after the data were analyzed descriptively. The risk factors that prominent that make Baliinfected rabies include: dogs kept by releasing freely; presence of rabies carrier animals other than dogs;dog free contact with other dogs; the dogs were kept without having fed; puppies obtained from others; theflow of the dogs in and out to the village; And many communities have not obtained adequate counselingregarding the rabies. The conclusion that may be drawn is that there are some of factors that make Baliremain infected rabies.
Keywords: rabies, rabies infected areas, the driving factor